2002
DOI: 10.1034/j.1399-3089.2002.0o144.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid failure of pig islet transplantation in non human primates

Abstract: We have previously demonstrated that adult pig islets of Langerhans are not destroyed in vitro by primate sera. Whether these islets can function when placed into the liver of non-human primates is not known. We now report on the outcome of pig islet xenotransplantation into five non diabetic primates (four baboons and one macacus fascicularis) receiving intraportally purified adult pig islets. The average number of islet-equivalent per graft was 110,000 (60-180,000). All animals received associations of ATG, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 27 publications
2
57
0
Order By: Relevance
“…In nonhuman primates, the function of adult pig islets in both nondiabetic and diabetic immunosuppressed animals has been shown to be very short lasting, indicating almost immediate graft destruction in this species Cantarovich et al 2002). In contrast, a regimen including splenectomy and irradiation prolonged graft survival to more than 2 wk, although it failed to prevent rejection thereafter .…”
Section: Transplantationmentioning
confidence: 99%
“…In nonhuman primates, the function of adult pig islets in both nondiabetic and diabetic immunosuppressed animals has been shown to be very short lasting, indicating almost immediate graft destruction in this species Cantarovich et al 2002). In contrast, a regimen including splenectomy and irradiation prolonged graft survival to more than 2 wk, although it failed to prevent rejection thereafter .…”
Section: Transplantationmentioning
confidence: 99%
“…Therefore, it is important to note that when adult pig islets have been transplanted intra-portally into baboons, the xenografts were destroyed within a few days despite receiving strong immunosuppression. Cantarovich et al [14] infused adult pig islets (11 000 IEQ/kg; range 6000-50 000) into the portal circulation of five non-diabetic primates (four baboons and one macaque). All grafts failed within 3 days despite immunosuppression with cyclosporin, mycophenolate mofetil, ATG and high-dose methylprednisolone.…”
Section: Results Of Islet Cell Xenotransplantation In Humans and Primmentioning
confidence: 99%
“…Two studies have shown rapid destruction of adult pig islets transplanted intraportally into baboons, with few or no viable islets remaining by day 2 and evidence of thrombosis and deposition of antibody and complement [13,14]. A pig-to-macaque model showed destruction of most islets within 3 days, with early deposition of humoral components, although in this case rejection was predominantly mediated by an acute cellular mechanism with little evidence of intraportal thrombosis [2 ].…”
Section: Use Of Fetal and Newborn Islet-like Cell Clusters As A Sourcmentioning
confidence: 99%
“…Diffuse, presumably nonspecific IgG deposits were noted within islet-associated platelet accumulations 12 h after transplantation. Considerable IgM and moderate-tostrong C3, C5, and C9 depositions were present on islet surfaces 2-3 days after xenograft [54][55][56]. Antigalactosyl (anti-Gal) and non-Gal [57,58] IgM antibodies bind to islet surfaces soon after transplantation and activate the classic complement pathway and neutrophil infiltration.…”
Section: Immunological Hurdles For Pig Islets Xenotransplantationmentioning
confidence: 99%